Analisis Multidimensional Peran Bank Syariah Dalam Meningkatkan Daya Saing Industri Kecil Menengah Sepatu Sandal Di Mojokerto - Lely Maharani; Mugiyati Mugiyati; Ony Thoyib Hadi Wijaya (Program Studi Ekonomi Syariah, STAI AN-NAJAH INDONESIA MANDIRI, 2026)
This study aims to analyze the contribution of Bank Syariah Indonesia (BSI) to improving competitiveness of the small and medium scale footwear industries in Sooko District, Mojokerto through a multidimensional approach encompassing financial, social, and spiritual aspects. A qualitative descriptive approach was employed, using in-depth interviews, participatory observation, and documentation. Informants included five footwear producers and one representative from BSI Mojokerto. Data analysis used Miles and Huberman's interactive model with source and method triangulation for data validity. The results reveal that BSI's contribution is holistic, not limited to financing through sharia contracts such as murābaḥah and muḍārabah, but also includes capacity building through financial management training, sustainable business mentoring, and sharia financial literacy improving competitiveness. BSI acts as a strategic partner to enhance managerial capacity, expand market access, and promote business sustainability among small-scale entrepreneurs. Findings show an average production capacity increase of 20-30%, and adoption of digital marketing technology among BSI-partnered businesses. Nevertheless, challenges remain, particularly in sharia literacy, digital access limitations, and financing procedure complexity. The study concludes that Islamic banks play a crucial role in strengthening an equitable and sustainable sharia economic ecosystem at the grassroots level through the implementation of maqāṣid al-syarī'ah values, particularly in preserving wealth (ḥifẓ al-māl) and life (ḥifẓ al-nafs). Kata Kunci: Islamic Bank, Islamic Financing, Small and Medium Industries, Economic Empowerment